In Vitro Microleakage of Bulk Fill and Conventional Composites and a Hybrid Glass Ion-omer in Primary Molars - Tolouei, Alaleh; ghasemi, amir; askarizadeh, nahid (Journal of Dental School, 2020)
Objectives The main disadvantage of composite resins is their polymerization shrinkage, which can lead to microleakage. The purpose of this in vitro study was to evaluate the microleakage of bulk fill and conventional composites and a new hybrid glass ionomer (GI) in class II restorations of primary molar teeth. Methods In this in vitro study, 51 primary molar teeth were randomly divided into three groups. Standard class II cavities were then prepared. In group 1 the cavities were restored with Filtek bulk fill composite; in group 2, the cavities were incrementally filled with Z250 conventional composite and in group 3, EQUIA Forte hybrid GI resin was used to fill the cavities. The teeth were subjected to thermal and then mechanical thermocycling. Afterwards, the teeth were immersed in 1% methylene blue solution. The teeth were then mesiodistally sectioned, and microleakage was evaluated at the occlusal and gingival margins under a stereomicroscope and a scanning electron microscope (SEM). The Shapiro-Wilk and Kruskal-Wallis tests were used to statistically analyze the data. Results There was no statistically significant difference in the mean microleakage of bulk fill and conventional composites and hybrid GI in the occlusal (P=0.495) or gingival (P=0.293) margins. The gingival microleakage was significantly higher than occlusal microleakage in all three groups (P<0.05). Conclusion Based on the results of the present study, microleakage of Filtek bulk fill composite is the same as that of Z250 conventional composite and EQUIA Forte hybrid GI.